SIMBOLISASI YESUS DALAM TASAWUF (Al'Adalah, 2002)
Tasawuf is an effort oj creatures to clean their heart and thought from material-tendency (worldly life), then fulfill them with dzikir (strong awareness of Allah) so (hat they achieve ma'rifah (vision) and union. Al-Ghazali is known as a character of tasawuf that tries to return the teaching of tasawuf to the teaching of the companions and tabi'in of the Prophet. Namely tasawuf sunni. But he frequently of the companions and to reveal symbolization of Yesus in his life of tasawuf. Moreover, in developing his tasawuf thought, Ibn Araby, known as a continuator of the view of pholosophical tasawuf, made use of philosophical reference and Bibel more than what Al-Ghazali did. It means that the point of contact between the life of tasawuf and the religious life of the earlier mankind cannot be avoided. This also happenend to the development of ilmul-fiqh, Theology, Islamic Philosophy and ilmul-akhlaq. This constitutets the reason that out of all islamic knowledge, ilmu-tasawuf gets most attenttion and criticsm in the case of it's authenticity form many people including the Wahaby followers. Whereas, actually tasawuf in Islam is the core of all teaching so Al-Ghazali calls it as Asrar al-Iman, the core of syari'at (fiqh) or called as Asrar al-Salah, and the core of Akhlaq or called as Asrar Birri al-Walidain.